REVISITING THE GOLDEN RULE IN ACCOUNTING: A NORMATIVE INQUIRY INTO JUSTICE, FAIRNESS, AND EQUITY - Bamidele Vincent Olawale; Abdulsallam Dauda (PT. ZILLZELL MEDIA PRIMA, 2025)
This paper examines the application of the ethical principle of the Golden Rule, “Treat others as you wish to be treated,” in a framework of accounting professions. It is notable that justice and fairness, or equity, are accepted elements of accounting’s legitimacy, value, and social worth; nevertheless, a full application of the Golden Rule in accounting theory and practice has not been realized. This work aims at establishing a normative model rooted in the Golden Rule to account for distributive, procedural, and corrective injustice in accounting, drawing from differing philosophical, religious, and ethical works. This model demonstrates how the Golden Rule can help resolve ethics-based dilemmas related to financial reporting, auditing, taxation, and professional practices by cultivating empathy and reciprocal responsibility, which can be termed attitudinal accountability among professionals. This paper also outlines actionable recommendations for educators as well as setters of standards and practitioners within prescribed professional networks. Policy initiatives researched are on the implementation forefront. Ultimately this paper argues that the profession of accounting advocating moral culture with the Golden Rule will restore public confidence while providing better opportunities for all stakeholders.